2022
DOI: 10.21037/apm-22-102
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between peripheral blood inflammatory markers and diabetic macular edema in patients with severe diabetic retinopathy

Abstract: Background: Diabetic macular edema (DME) is a serious complication of diabetic retinopathy (DR).Recent studies have shown that inflammation is closely associated with the development of DME, and peripheral blood inflammatory markers [white blood cell (WBC) count and its subtypes] are relatively simple and easy to detect. Here, we investigated the relationship between peripheral blood inflammatory markers and macular edema in patients with severe DR (including both severe non-proliferative DR and proliferative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…As a recognized indicator of inflammation, lymphocytes are actively involved in the elimination and repair of inflammation. Zhu et al found that a lower lymphocyte percentage might potentially serve as a valuable diagnostic indicator for identifying the onset and progression of diabetic macular edema (DME) (26). Platelets play a crucial role in diabetes patients through heightened adhesion, activation, and aggregation of platelets due to disruptions in multiple signaling pathways and metabolic abnormalities such as hyperglycemia and dyslipidemia (27).…”
Section: Discussionmentioning
confidence: 99%
“…As a recognized indicator of inflammation, lymphocytes are actively involved in the elimination and repair of inflammation. Zhu et al found that a lower lymphocyte percentage might potentially serve as a valuable diagnostic indicator for identifying the onset and progression of diabetic macular edema (DME) (26). Platelets play a crucial role in diabetes patients through heightened adhesion, activation, and aggregation of platelets due to disruptions in multiple signaling pathways and metabolic abnormalities such as hyperglycemia and dyslipidemia (27).…”
Section: Discussionmentioning
confidence: 99%
“…For peripheral blood lymphocytes, Zhu et al. ( 23 ) found the inverse relationship between and DME, indicating that for patients suffering from severe DR, lymphocyte percentage may be an important diagnostic tool for detecting the onset and progress of DME. Our results showed a critical association between DME and lymphocyte counts, but no association between CMT and lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…The complete blood count is an affordable and readily available test; white blood cell (WBC, also known as leukocyte) and its subtypes are considered to be the biomarkers of inflammatory response, as their activation results in the synthesis of inflammatory cytokines. Recently, increasing concern has been demanded regarding WBC and its subtypes and its relations in several ocular inflammatory conditions such as uveitis ( 17 19 ), DR ( 20 22 ), and DME ( 23 25 ). All these inflammation indexes derived by peripheral complete blood count parameters including the neutrophil-to-lymphocyte ratio (NLR) ( 24 , 26 ) and systemic immune-inflammation index (SII, calculated as platelet count*neutrophil count/lymphocyte count) ( 24 , 27 ) have been investigated as potential biomarkers for predicting or guiding treatment in DME.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that ( 26 ) Platelets and neutrophils interact with each other, and under inflammatory stimulation neutrophils produce platelet chemokines and activating factors, and activated platelets release large amounts of pro-inflammatory and pro-angiogenic factors that damage vascular endothelial cells, leading to increased vascular permeability, edema, and exudation, which further activate neutrophils to release more inflammatory mediators and induce chronic microangiopathy and inflammatory responses ( 26 ), promoting DN ( 27 ) and DR ( 28 ) of progression. Recent findings suggest that Lymphocyte percentage can be used as an inflammatory marker for the development of DME in patients with severe DR ( 29 ).The NLR and PLR in the DR/DN group in this study were significantly higher than those in the DR group, suggesting a more severe inflammatory response in DR/DN; previous studies also found that NLR predicted DN progression ( 30 ) and the severity of DR ( 31 ); a recent study ( 32 ) demonstrated that NLR and PLR are risk factors for DN and may be predictors of early DN patients ( 33 ); another study ( 34 ) also showed that NLR was an independent risk factor for DR, DN, and DR/DN, Latest Research suggest that PLR may be an independent risk factor for evaluating DR in type 2 diabetes patients ( 35 ).The present study found that both NLR and PLR were independent risk factors for DR/DN, and the risk of DR complicated by DN was significantly increased when PLR > 103.73. Previous studies found that PLR also predicted diabetes-related lower extremity vascular disease ( 36 ), atherosclerosis and diabetic foot ulcers ( 37 ).…”
Section: Discussionmentioning
confidence: 99%